Optimal treatment strategy and prognostic analysis for patients with locally advanced Upper Tract Urothelial Carcinoma - Jiang, Fan; Dai, Ruijie; Zhou, Mingguo; Cao, Xuefei; Lu, Jun; Zheng, Xinyu (Frontiers in Surgery, 2025)
ObjectiveThis study aims to identify the optimal treatment strategy and conduct a prognostic analysis for patients with locally advanced Upper Tract Urothelial Carcinoma (UTUC).Methods and materialsThe study included 3,829 patients diagnosed with pT3-4N0/+M0 UTUC from 2004 to 2015, with data obtained from the Surveillance, Epidemiology, and End Results (SEER) database. Patients were randomly assigned to a training group (70%) and a validation group (30%) for nomogram development. Variables that were significant in univariate COX regression analysis (P < 0.05) were included in the multivariate COX regression model, and a nomogram was formulated based on the variables that remained statistically significant (P < 0.05) in the multivariate analysis. The nomogram's predictive precision and ability to differentiate were evaluated through the concordance index(C-index), area under the curve (AUC), and calibration curves. The model's clinical validity was confirmed through the use of decision curve analysis (DCA).ResultsWithin the pN+ subgroup, the combination of surgery with both adjuvant chemotherapy and radiotherapy (S + R + C) group and S + C group yielded superior results over the S group, with the S + R + C group regimen showing the most favorable outcomes. The 3-year OS rates for patients in the S + R + C, S + C, and S groups were recorded as 40.00%, 31.43%, and 12.5%. The corresponding 3-year CSS rates were 47.56%, 34.02%, and 17.5%. Multivariate COX regression analysis identified age, primary tumor location, T and N stages, treatment modality, tumor size, and lymph node count as significant predictors of OS and CSS. These factors were integrated into precisely developed nomograms for predicting OS and CSS, with concordance indices of 0.651 and 0.667 in both sets.ConclusionFor patients with pT3-4N + M0 stage UTUC, the addition of radiotherapy to the surgical and chemotherapy regimen has proven to enhance survival rates. Our predictive nomogram reliably forecasts OS and CSS rates for locally advanced patients. This tool can assist clinicians in identifying high-risk individuals, thereby aiding in the formulation of informed treatment decisions.